1996
DOI: 10.1007/bf00225722
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of Dipterocarpaceae in Southeast Asia using RFLP of PCR-amplified chloroplast genes

Abstract: Dipterocarpaceae is the dominant family of Southeast Asia's climax tropical rain forest region, and it contains the region's most important commercial timber species. A molecular phylogeny of the Dipterocarpaceae subfamily Dipterocapoideae was constructed using restriction fragment length polymorphisms of polymerase chain reaction-amplified specific genes in chloroplast DNA. A total of 141 site changes were detected among ten genera and 30 species in 11 different genes: rbcL, psbA, psbD, rpoB, rpoC, petB, atpH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…The mat K gene sequence is one of the seven loci widely utilized for the DNA barcoding of plants (Babbar et al 2012). Specific chloroplast genes and/or intergenic spacers can be amplified (Taberlet et al 1991; Demesure et al 1995; Tsumura et al 1995, 1996; Dhingra and Folta 2005; Heinze 2005). The amplicons can be directly sequenced or restriction endonuclease digested (PCR–RFLP or cleaved amplified polymorphic sequence), and the occurrence of microsatellites (cpSSRs) in the chloroplast genome has been widely utilized for species identification, reconstruction of phylogenetic relationships, taxonomic studies and the identification of maternal parents in polyploids (Tsumura et al 1995, 1996; Weising and Gardner 1999; Ishii and McCouch 2000; Lakshmi et al 2000; Parani et al 2000, 2001; Komatsu et al 2001; Provan et al 2001; Kishimoto et al 2003; Nwakanma et al 2003; Zhu et al 2003; Asadi Abkenar et al 2004, 2008; Van Droogenbroeck et al 2004; Ibrahim et al 2007; Angioi et al 2008; Sehgal et al 2008; Jena et al 2009; Liu et al 2011; Poczai et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The mat K gene sequence is one of the seven loci widely utilized for the DNA barcoding of plants (Babbar et al 2012). Specific chloroplast genes and/or intergenic spacers can be amplified (Taberlet et al 1991; Demesure et al 1995; Tsumura et al 1995, 1996; Dhingra and Folta 2005; Heinze 2005). The amplicons can be directly sequenced or restriction endonuclease digested (PCR–RFLP or cleaved amplified polymorphic sequence), and the occurrence of microsatellites (cpSSRs) in the chloroplast genome has been widely utilized for species identification, reconstruction of phylogenetic relationships, taxonomic studies and the identification of maternal parents in polyploids (Tsumura et al 1995, 1996; Weising and Gardner 1999; Ishii and McCouch 2000; Lakshmi et al 2000; Parani et al 2000, 2001; Komatsu et al 2001; Provan et al 2001; Kishimoto et al 2003; Nwakanma et al 2003; Zhu et al 2003; Asadi Abkenar et al 2004, 2008; Van Droogenbroeck et al 2004; Ibrahim et al 2007; Angioi et al 2008; Sehgal et al 2008; Jena et al 2009; Liu et al 2011; Poczai et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The PCR-RFLP approach to study organellar genome diversity has been reported in many plants (Tsumura et al, 1995(Tsumura et al, , 1996Lakshmi et al, 2000;Parani et al, 2000Parani et al, , 2001Komatsu et al, 2001;Kishimoto et al, 2003;Nwakanma et al, 2003;Zhu et al, 2003;Asadi Abkenar et al, 2004Van Droogenbroeck et al, 2004;Ibrahim et al, 2007;Sehgal et al, 2008;Jena et al, 2009;Poczai et al, 2011). This work aimed at deciphering the polymorphism in the chloroplast and mitochondrial genomes in the Saccharum spp.…”
Section: Discussionmentioning
confidence: 99%
“…Specific chloroplast genes and/or intergenic spacers can be amplified (Taberlet et al, 1991;Demesure et al, 1995;Tsumura et al, 1995Tsumura et al, , 1996Dhingra and Folta, 2005;Heinze, 2007). The amplicons can be directly sequenced or restriction endonuclease digested (PCR-RFLP) or subjected to cleaved amplified polymorphic sequence (Tsumura et al, 1995(Tsumura et al, , 1996Lakshmi et al, 2000;Parani et al, 2000Parani et al, , 2001Komatsu et al, 2001;Kishimoto et al, 2003;Nwakanma et al, 2003;Zhu et al, 2003;Asadi Abkenar et al, 2004Van Droogenbroeck et al, 2004;Ibrahim et al, 2007;Sehgal et al, 2008;Jena et al, 2009;Poczai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The availability of universal primers capable of amplifying specific regions of the chloroplast (BADENES and PARFITT, 1995;TSUMURA et al, 1996;Heinze B, 2001) genomes using the polymerase chain reaction (PCR) has made it possible to explore organelle DNA diversity for taxonomic and phylogenetic purposes. Because of its uniparental mode of inheritance and its low mutation rate related to the nuclear genome, the chloroplast DNA (cpDNA) is considered to be an ideal system in phylogeny and in population genetics.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its uniparental mode of inheritance and its low mutation rate related to the nuclear genome, the chloroplast DNA (cpDNA) is considered to be an ideal system in phylogeny and in population genetics. Currently, sequence comparison or restriction analysis of fragments amplified with universal primers for organellar DNA has been widely used in species identification, genetic diversity and phylogenetic studies in many different plant species (GIELLY and TABERLET 1994;BADENES and PARFITT et al 1995;DEMESURE et al 1996;TSUMURA et al 1996;PARDUCCI and SZMIDT 1999;HUANG and SUN 2000;PARANI et al 2000PARANI et al , 2001WANG et al 2000;XU et al 2001;WU et al 2005).…”
Section: Introductionmentioning
confidence: 99%